Endoscopic Endonasal Transsphenoidal Surgery for Recurrent Craniopharyngiomas - Feng, Zhenguang; Li, Chuzhong; Cao, Lei; Qiao, Ning; Wu, Wentao; Bai, Jiwei; Zhao, Peng; Gui, Songbai (Frontiers in Neurology, 2022)
Object: Although revision surgery for recurrent craniopharyngiomas is more challenging than primary surgery, and often accompanies with a higher risk of death and complications, the endoscopic endonasal transsphenoidal surgery (EETS) is sometimes still an effective and reliable treatment option. In the study, we introduced the surgical outcomes of EETS for the recurrent craniopharyngiomas, and summarized the surgical experiences. Methods: Between 2014 and 2018, 28 patients with recurrent craniopharyngiomas underwent 29 endoscopic endonasal transsphenoidal surgeries in our department. We regarded the patient undergoing two EETS as two independent patients in statistical analysis. Of the 29 patients, 16 had undergone 1 previous surgery, 10 had undergone 2 previous surgeries, and the remaining 3 patients had undergone 3 surgeries. The extent of resection, visual and endocrine outcomes, complications of all the patients were collected and analyzed. Results: Gross total resection was accomplished in sixteen patients (55.17%), subtotal resection in 11 patients (37.93%), partial resection in 2 patients (6.9%). Among the 22 patients with preoperative visual acuity and visual field impairment, some degree of vision improvement was observed in 18 patients, 3 patients was without visual change, perpetual deterioration of vision occurred in one patient. The remaining 6 patients had normal vision before and after surgery. Postoperative endocrine tests showed that among 5 patients with normal preoperative pituitary hormone function, only 1 patient still got normal pituitary hormone function, the other 4 patients got one or more hypothalamic pituitary axes involved. None of the patients with preoperative endocrine dysfunction had endocrine function improved. DI were observed in six new cases postoperatively. Cerebrospinal fluid (CSF) leakage occurred in 1 patient. One patients had bacterial meningitis and was cured with antibiotic treatment and a lumbar drain. No serious morbidity and mortality occurred in all patients. Conclusions: For recurrent craniopharyngiomas, a personalized treatment plan should be developed according to the tumor characteristics and the patient's situation. There is not an omnipotent method to be used for all patients. The EETS still is a safe, effective way to treat recurrent craniopharyngiomas in the appropriate patients. Key words: craniopharyngiomas; recurrent craniopharyngiomas; endoscopic endonasal transsphenoidal surgery